Participation of young children with developmental disabilities: parental needs and strategies, a qualitative thematic analysis - Dominique Van de Velde; Marieke Coussens; Floris Vitse; Annemie Desoete; Guy Vanderstraeten; Hilde Van Waelvelde (BMJ Open)
Objectives Participation refers to a person’s involvement in activities and roles that provide interaction with others as well as engagement in family and community activities. Young children with developmental disabilities (DD) such as attention deficit hyperactive disorder, autism spectrum disorder and developmental coordination disorder are limited in their participation compared with their typically developing peers. This study aimed to obtain information regarding parental needs and strategies used to enable their child’s participation.Design A thematic inductive approach with in-depth interviews was used to explore parental experiences. Eleven women and two men, between 30 and 40 years of age, who had a child (4–9 years old) with a DD diagnosis based on Diagnostic and Statistical Manual of Mental Disorders criteria, participated in semistructured interviews.Results Two central themes emerged: parental needs and parental strategies used to enable their child’s participation. Parental needs were the following: increasing awareness, ameliorating parental burden, providing tailored interventions and supporting parents in finding suitable leisure activities. Parental strategies aimed at increasing their child’s resiliency, attaining maximal fit between activity requirements and child capacity, and creating inclusive opportunities and awareness.Conclusions Understanding what families’ needs are and how families use and integrate strategies within the context of their daily lives provides practitioners with insights needed to support families’ resiliency in promoting their children’s participation. The results have implications for professionals as this information can be used to inform, refine, or tailor participation-based and family-centred services.